Structures and Properties of Two New Three‐Dimensional Inorganic‐Organic Hybrid Compounds Based on Isopolymolybdate Clusters. Issue 2 (15th December 2015) - Wang, Jingjing; Yin, Xuena; Mu, Bao; Li, Na; Huang, Rudan
Abstract: Two new inorganic‐organic hybrid materials containing different isopolymolybdate units, namely, [{Ce(pdca)(H2 O)}{Ce(pdca)(H2 O)5 }]2 Mo8 O26 ·10H2 O (1 ), [Cu(phen)(H2 O)2 ]2 [Mo6 O20 ] (2 ) (pdca=pyridine‐2, 6‐dicarboxylic acid, phen=1, 10‐phenanthroline) have been successfully synthesized under hydrothermal conditions, and characterized by elemental analyses, IR spectra, thermal gravimetric analyses (TGA), single‐crystal X‐ray diffraction and powder X‐ray diffraction (PXRD). In compound1, Ce(III) ions are bridged by pdca ligands to form cerium‐organic coordination layers, which are further pillared by octamolybdate clusters via the covalent bonding of CeO, leading to the formation of a 3D pillar‐layered open‐framework architecture. Compound2 features a 3D supramolecular structure constructed by hydrogen bond interactions between 1D molybdate chains aggregated by [Mo6 O20 ] 4− polyoxoanions and coordinated water molecules. It was remarkable that H3 [PMo12 O40 ]· Χ H2 O decomposes into hexamolybdate anions, which are linked together with phen ligands by Cu(II) cation. Moreover, UV‐vis spectra and fluorescence properties of compounds1 –2 have also been investigated in detail. Abstract : Compound1 features the 3D pillar‐layered framework structures assembled by 2D cerium‐organic coordination sheets pillared by β ‐[Mo8 O26 ] 4− clusters. Compound2 exhibits a 3D supramolecular structure containing [Mo6 O20 ] 4− polyoxoanions‐based 1D molybdate chains through hydrogen bond interactions. The UV‐vis spectra and fluorescence properties of compounds1 –2 have also been investigated in detail.